New route for the synthesis of propylene glycols via hydroformylation of vinyl acetate - Borole, Yogesh L.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
Hydroformylation of vinyl acetate (VAM) has been studied as a key step in the alternative route for the synthesis of 1,2-propanediol (1,2-PDO) and 1,3-propanedol (1,3-PDO) using homogeneous rhodium (Rh) and cobalt (Co) complex catalysts. The feasibility of the VAM hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step using homogeneous Rh and Co catalysts. The roles of the catalyst precursors, ligands, and solvents in the activity and regioselectivity of the aldehyde products, i.e., 2-acetoxy propanal (2-ACPAL) and 3-acetoxy propanal (3-ACPAL), and the effect of reaction conditions have been investigated. With Rh-phosphine catalysts, 2-ACPAL is obtained with a selectivity of > 90%, while with cobalt carbonyl catalyst, 2-ACPAL and 3-ACPAL are formed with comparable selectivities (similar to 50% each) thus substantially improving the selectivity of the linear aldehyde, a precursor for 1,3-PDO. In halogenated solvents with cobalt carbonyl catalyst, the selectivity to 3-ACPAL was found to increase still further (58%). A possible mechanism to explain the variation in regioselectivity for the Rh anal Co catalysts has been discussed. In the presence of pyridine as a ligand in the Co-catalyzed hydroformylation of VAM, the rate of reaction was found to be enhanced 4-fold. The hydrogenation of acetoxypropanal isomers using Raney-Ni catalyst followed by hydrolysis using Amberlite IR-120 resin catalyst gave quantitative conversion to the mixture of 1,2- and 1,3-PDOs (> 90% yield).
Joint 5th International Symposium on Catalysis in Multiphase Reactors/4th International Symposium on Multifunctional Reactors, Portoroz-Portorose, SLOVENIA, JUN 15-18, 2005